2003
DOI: 10.1093/ajcn/77.5.1324
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and bone mineral density in early postmenopausal women

Abstract: In younger postmenopausal women ( age: 56 y) whose average baseline serum 25-hydroxyvitamin D concentration was well within the normal range, the addition of 10 000 U vitamin D(2)/wk to calcium supplementation at 1000 mg/d did not confer benefits on BMD beyond those achieved with calcium supplementation alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 24 publications
5
60
2
1
Order By: Relevance
“…20 Several studies have documented stability or an increase in BMD in IBD patients given calcium and vitamin D supplements. [21][22][23][24] These findings are consistent with observational studies [25][26][27] and randomized trials [28][29][30][31] Although this study has focused on the skeletal actions of vitamin D, this hormone also has important physiological actions outside of the musculoskeletal system. 32 Receptors for calcitriol and the enzyme involved in its synthesis (1-hydroxylase) are expressed by many tissues other than those concerned with calcium regulation, and in some tissues there appear to be important antiproliferative and prodifferentiating properties.…”
Section: Discussionsupporting
confidence: 80%
“…20 Several studies have documented stability or an increase in BMD in IBD patients given calcium and vitamin D supplements. [21][22][23][24] These findings are consistent with observational studies [25][26][27] and randomized trials [28][29][30][31] Although this study has focused on the skeletal actions of vitamin D, this hormone also has important physiological actions outside of the musculoskeletal system. 32 Receptors for calcitriol and the enzyme involved in its synthesis (1-hydroxylase) are expressed by many tissues other than those concerned with calcium regulation, and in some tissues there appear to be important antiproliferative and prodifferentiating properties.…”
Section: Discussionsupporting
confidence: 80%
“…The effect of calcium, however, was greater when the serum vitamin D levels were lower [23]. Cooper et al [24] reported that the change in BMD in early postmenopausal women did not differ significantly between women taking calcium alone and those taking calcium and vitamin D2 supplements together.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical trials evaluating the effect of vitamin D supplementation on loss of bone density in midlife have produced conflicting results. [11][12][13][14][15] Some of these trials have combined calcium with vitamin D supplements, so that it is unclear which nutrient is responsible for the observed benefit. 7,8,16 Another confounding factor in interpreting previous trials is that reducing bone resorption may result in a temporary alteration in the remodeling space with an increase in bone density that is limited to the length of the remodeling cycle.…”
Section: Here Is Consensus On Thementioning
confidence: 99%